ELEVATING READING COMPREHENSION THROUGH THINK-PAIRED-SHARE (TPS) TECHNIQUE - Ahmad Zulbani; Iis Sujarwati (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
Reading plays a significant role in the academic performance and critical thinking abilities of students. Teachers face challenges such as diverse reading abilities among students, which can hinder effective teaching practices. TPS has been identified as a potential technique to address the challenge by promoting active and interactive learning. However, limited research has examined the impact of TPS on reading comprehension in junior high school contexts. Therefore, additional empirical evidence is required to assess its effectiveness in this domain. This research aims to evaluate the effectiveness of the Think Pair Share technique in elevating reading and improving reading comprehension among junior high school students. This study used an experimental approach involving a pre- and post-test design. One class employed the TPS technique as the experimental class, whereas the other class followed a conventional learning approach as the control class. The mean score for the experimental class was 78.67, in contrast to 70.33 for the control class was 70.33. The findings demonstrate an improvement in reading comprehension in the experimental class compared with the control class. This study provides evidence for the effectiveness of the Think Pair Share technique in elevating reading comprehension in junior high school students.